The effect of plasma rich platelet graft on post‐operative complications in mid‐penile hypospadias. (20th May 2020) - Eryilmaz, Recep; Şimşek, Metin; Aslan, Rahmi; Beger, Burhan; Ertaş, Kasım; Taken, Kerem
Abstract: Hypospadias is one of the most common penile congenital anomalies, which often requires a surgical approach. After the hypospadias is repaired, urethral fistula can occur in around 20% of patients. In this study, we used platelet‐rich plasma (PRP) to reduce the urethral fistula and other post‐operative complications after hypospadias repair. Only patients with primary mid‐penile hypospadias were included study. Patients with forms other than mid‐penile hypospadias and cases with previous hypospadias surgery were excluded from the study. A total of 40 hypospadias patients were included in this study. These patients were divided into groups A and B with 20 patients in each group. Hypospadias repair was performed with the Snodgrass TIPU technique on both groups. PRP was used with group A, and PRP was not use with group B. These two groups were compared in terms of early and long‐term post‐operative complications. Both early and long‐term post‐operative UCF, urethral stenosis and post‐operative infection rates were lower in the group using PRP, group A. PRP has the potential to prevent post‐operative complications occurring after hypospadias repair, particularly post‐operative infection.